Analyzing Linguistic Characteristics of Paraphrase in Second Language (L2) Writing - Awang @ Hashim, Nazratul Akmal (Pusat Pengajian Ilmu Kemanusiaan, 2019)
Paraphrasing serves as a fundamental skill in academic writing which requires students to understand and respond to a specific written passage. The skill allows students to borrow the ideas of an author and rewrite them in their own words. Students in L2 contexts particularly, use paraphrasing as an important borrowing strategy when integrating source text into their writing. Campell (1998) defines paraphrasing as "using different phrasing and wording (requiring citation) to express a particular passage that was originally written or spoken by someone else, in order to blend the other’s idea smoothly into one’s own writing" (p. 86). Meanwhile, Uemlianin (2000) defines paraphrasing as “the reproduction of the information content and structure of source text” (p. 349). There is no consensus regarding paraphrasing in academic writing although the skill is very crucial to avoid plagiarism. According to Keck (2006), writing at tertiary level requires students to synthesize information from previous literature whenever they want to complete their assignments. This is due to the fact that the idea of a text is a result of previous texts the writer has encountered, which means the written texts cannot be totally original (Pennycook, 1996).